COMPARISON OF EXPERIMENTAL TECHNIQUES TO INCREASE THE NUMBER OF MEASURABLE CONFINED FISSION TRACKS IN ZIRCON - Yamada R.; Yoshioka T.; Watanabe K.; Tagami T.; Nakamura H.; Hashimoto T.; Nishimura S. (My University, 1998)
We compared three experimental techniques for increasing the number of measurable horizontal confined fission tracks (HCTs) in annealed and unannealed zircon. These techniques are irradiation of 252Cf spontaneous fission fragments, irradiation of heavy ions (58Ni11+) using a tandem van de Graaff accelerator, and artificial fracturing of the zircon grains. All these techniques increased the number of measurable HCTs and they introduced no significant change in the measured length of annealed HCTs. For the samples with low track density (~105 cm-2), heavy ion irradiation was far more effective than irradiation of 252Cf fission fragments, because relatively long artificial tracks could be formed by the heavy ion irradiation. The artificial fracturing method is recommended when an accelerator facility is not easily available, because its effect was comparable to heavy ion irradiation and it is practicable in ordinary laboratories. Using these techniques, a preliminary comparison of annealing characteristics was performed for three zircon samples with different spontaneous track densities of ~4.105, ~4.106 and ~2.107 cm-2 (with fission track ages of 3.1, 22.8 and 367.6 Ma, respectively). The length reduction due to the thermal annealing of these zircons appeared to be different, with the possibility that the thermal stability of spontaneous fission tracks depends on the initial spontaneous track density (i.e., the higher the initial spontaneous track density of a sample, the slower the rate of track annealing).
Keywords: FISSION TRACK; CONFINED TRACK LENGTH; THERMAL HISTORY; ACCELERATOR; 252CF